Human rights in the biotechnology era 1 - Benatar Solomon R (BMC, 2002)
Abstract Backgound The concept of Human Rights has become the modern civilising standard to which all should aspire and indeed attain. Discussion In an era characterised by widening disparities in health and human rights across the world and spectacular advances in biotechnology it is necessary to reflect on the extent to which human rights considerations are selectively applied for the benefit of the most privileged people. Attention is drawn particularly to sub-Saharan Africa as a marginalised region at risk of further marginalisation if the power associated with the new biotechnology is not used more wisely than power has been used in the past. To rectify such deficiencies it is proposed that the moral agenda should be broadened and at the very least the concept of rights should be more closely integrated with duties Summary New forms of power being unleashed by biotechnology will have to be harnessed and used with greater wisdom than power has been used in the past. Widening disparities in the world are unlikely to be diminished merely by appealing to human rights. We recommend that a deeper understanding is required of the underlying causes of such disparities and that the moral discourse should be extended beyond human rights language.